Inter-organization communication management between organizations in a subsidized fertilizer market in Malaysia - Ammar Redza, Ahmad Rizal; Shahrina, Md Nordin; Shamsuri, Md Saad; Hasnida, A. W. (Elsevier, 2014)
Inter-Organization Communication (IOC) is one of the used communication disciplines to communicate between two or more organizations. It is proven vital to sustain relationship between organizations particularly between consumers and suppliers. However, there is still lack of empirical research and findings in the subsidized market. Malaysian paddy farmers have been receiving fertilizers subsidy since 1971 making the environment of subsidized market stand more than 40 years long. The relation between Area Farmer Organization known as Pertubuhan Peladang Kawasan (PPK) and the subsidized fertilizer supplier has now extended to 30 years. PPKs are responsible on the procurement process of the subsidized fertilizer from the supplier. This paper presents a preliminary findings based on IOC theories of communication management between PPKs and the supplier based on the perspectives of the PPK. It will critically discuss the elements of IOC and communication commitments based on the perspectives of PPKs. Thirteen PPKs from Kemubu Agriculture Development Authority (KADA) granary area were involved in this study. The results indicate organization communication willingness, behaviour, and quality as communication commitment of the PPKs